Bush kinder in Australia: A new learning 'place' and its effect on local policy. Issue 4 (May 2019) - Campbell, Coral; Speldewinde, Christopher
Bush kindergartens are a new practice in the Australian early childhood learning context and one that is rapidly becoming part of the kindergarten experience. Children leaving the confines of the bounded space of a kindergarten has been practised through excursions to outdoor places like zoos but the notion of conducting regular, ongoing kindergarten sessions away from the traditional kindergarten setting is one which is gaining momentum in Australian early childhood education, with possible impacts on future policy. In late 2014, a pilot programme titled 'Sandy Shores Kids Go Bush' was established across bush kindergartens in a region on the coastal fringe of south-eastern Australia using five existing sites. Each of these sites has differing characteristics impacting upon the experience of children attending the bush kinder programme. This paper reviews the settings of three different interpretations of 'bush kinder' and considers how the learning experience associated with bush kinder varies according to 'place' and how bush kinder has impact on both local and broader education policy.